Learn, unlearn, relearn : The new way of learning is called media and information literacy - Varga, Katalin; Egervári, Dóra (Tudásmenedzsment, 2022)
Media and information literacy is a key competency in the 21st century knowledge societies. It is much more than just knowing to use the digital technology. The media and information literate person knows how to learn, how knowledge is organized, and how to find, select, evaluate, organize and use information. The Institute of Library and Information Science at the University of Pécs made an online survey in 2014 about information competencies of university students all over Hungary. The aim of the survey was to get information about students’ information searching strategies, favourite resources, information seeking, selection and evaluation methods, and to base a new information literacy strategy. The results of this survey, compared with other surveys, show that during their studies students get a lot of assignments for which they need to find relevant information and literature, and analyzing them articulate a personal view about the problem. The biggest challenge for the new generation is the evaluation and selection of information. They don’t know how to make considered decisions, and very often they don’t even feel why this is important. That’s why it is crucial to develop special, professional information literacy competencies of students more efficiently. There is a special emphasis to be placed on the role of libraries, since they are the institutions that play a major role in the acquisition and development of information literacy. At the same time, this situation poses a serious challenge for libraries that they need to prepare for. There are international programs and projects that can help libraries in this endeavour.